2007
DOI: 10.1080/08820530701420082
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience After 1765 Intravitreal Injections of Bevacizumab: The Importance of Being Part of a Developing Story

Abstract: This retrospective report describes our 20 months'experience using intravitreal injections of bevacizumab for the treatment of several retinal diseases. We describe our experience after 1765 intravitreal injections of bevacizumab in the treatment of different proliferative retinopathies - retinopathy of prematurity, choroidal neovascularization, diabetic retinopathy, among others. We believe that the findings reported in this study move us closer to a better treatment for different pathologies. However, furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…All infants received intravitreal injections of ranibizumab 0.25 mg/0.025 ml (half dose of adult based on experience with bevacizumab (0.625 mg/0.025 ml) in the literature) 11 12. Treatment technique included topical anaesthesia, a standard aseptic skin and eyes preparation, local anaesthesia and insertion of a premature lid speculum followed by the intravitreal injection using a 27-gauge needle, 1 mm from the limbus.…”
Section: Methodsmentioning
confidence: 99%
“…All infants received intravitreal injections of ranibizumab 0.25 mg/0.025 ml (half dose of adult based on experience with bevacizumab (0.625 mg/0.025 ml) in the literature) 11 12. Treatment technique included topical anaesthesia, a standard aseptic skin and eyes preparation, local anaesthesia and insertion of a premature lid speculum followed by the intravitreal injection using a 27-gauge needle, 1 mm from the limbus.…”
Section: Methodsmentioning
confidence: 99%
“…Pathological and immunohistochemistry studies conducted using donkey anti-human IgG [25,26] showed a full-thickness retinal penetration into the RPE. In addition to its use for neovascular AMD, bevacizumab has also been analyzed for the treatment of choroidal neovascularization in pathologic myopia [28][29][30], diabetic retinopathy [31][32][33][34], macular edema caused by retinal vein occlusion [35][36][37], neovascular glaucoma and rubeosis iridis [38][39][40], pseudophakic cystoid edema [41] and retinopathy of prematurity [42,43], and turned out to be apparently safe and effective. Recently, intravitreal bevacizumab (IVB) has gained popularity also among vitreo-retinal surgeons for the management of diabetic eyes [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Quiroz-Mercado et al reported only a transient effect in the four eyes with Coats' disease that were injected with intravitreal bevacizumab. 32 While there was improvement in visual acuity and decrease of macular edema, regression of edema occurred after six weeks. However, the authors felt that while intravitreal bevacizumab might not be sufficient as initial treatment, it should still be considered for adjuvant therapy in the treatment of Coats' disease.…”
Section: Vegf Inhibition For Coats' Diseasementioning
confidence: 97%